2016
DOI: 10.1080/0167482x.2016.1235558
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of pain during oocyte retrieval

Abstract: The findings of the present study may help to identify those women who are at increased risk of experiencing unacceptable pain levels during oocyte retrieval procedures and the medical staff is advised to take psychological factors into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Aside from the administered analgesia, pain scores are also affected by psychosocial factors. A study by Frederiksen et al showed that women who had a high level of anxiety, a low level of perceived control, or negative gynaecological experiences in the past, reported higher pain scores [4]. These findings support the administration of an anxiolytic in order to reduce pain during oocyte retrieval.…”
Section: Discussionmentioning
confidence: 90%
“…Aside from the administered analgesia, pain scores are also affected by psychosocial factors. A study by Frederiksen et al showed that women who had a high level of anxiety, a low level of perceived control, or negative gynaecological experiences in the past, reported higher pain scores [4]. These findings support the administration of an anxiolytic in order to reduce pain during oocyte retrieval.…”
Section: Discussionmentioning
confidence: 90%
“…These unpleasant experiences could results in excessive worry about IVF treatment. 21 A research of Yoon Frederiksenet al 22 has shown that about 7% of women feel distressed during oocyte retrieval. Combined with the ndings in the present study, anesthetic measures should and could be taken to relieve the pain in women receiving oocyte retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Second, patient's anxiety before OR was not assessed in our study. Indeed, higher levels of anxiety during oocyte retrieval seem positively associated with pain intensity and anxiety [14][15][16].…”
Section: Discussionmentioning
confidence: 99%